Synergistic antifungal activity of antiretrovirals with amphotericin B against Aspergillus species - Ammar A. Khan; Ehab A. Salama; Mohamed N. Seleem (PLoS ONE, 2026)
Aspergillosis is a life-threatening fungal infection that primarily affects the lungs of immunocompromised individuals, including those living with human immunodeficiency virus (HIV), and is associated with mortality rates exceeding 50%. The infection is predominantly caused by Aspergillus fumigatus , a pathogen that has become increasingly difficult to treat due to the emergence of azole-resistant strains. Although azoles have traditionally served as first-line antifungals, the rise in resistance has necessitated broader use of amphotericin B (AmB), a polyene agent whose clinical utility is limited by its considerable toxicity. To address this therapeutic challenge, we screened a library of 618 antiviral compounds to identify agents that could synergize with AmB and enhance its antifungal efficacy. An initial screen identified 18 compounds that enhanced the antifungal activity of AmB. From this hit set, we prioritized the two FDA-approved HIV drugs, cobicistat and elvitegravir, as promising lead candidates. When combined with AmB, both compounds exhibited potent synergistic activity against A. fumigatus and other clinically relevant Aspergillus species, with FICI values <0.5 in over 90% of isolates tested. To further evaluate the breadth of this synergy, the assay was extended to include A. brasiliensis, A. flavus, A. niger , and A. terreus . Synergistic interactions were observed in three of the four species tested, while the combination displayed indifference against A. flavus . In time-kill assays, both combinations demonstrated sustained fungistatic effects over 48 hours and significantly impaired hyphal development as early as 16 hours, indicating early disruption of fungal growth. Additionally, both cobicistat and elvitegravir significantly enhanced the antibiofilm activity of AmB, reducing biofilm biomass by over 60% when combined with sub-inhibitory AmB concentrations. These combinations also disrupted mature biofilms, achieving up to 80% eradication, a substantial improvement over AmB alone. These findings highlight the potential of these drug combinations as promising treatment options for aspergillosis, leveraging already approved therapies.